Kebutuhan Nutrisi dan Substansi dalam Pakan Buatan Serangga (Artikel Ulasan) - I GEDE KETUT SUSRAMA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2017)
Insect Nutritional Requirements and Substances in its Artificial Diet In its life, insect as like as other creatures on earth need nutrients for the metabolism in their body so that the larval stage can grow to adult insect and then can do copulation to produce fertile eggs for its life cycle and for the existence sustainability of their species. Nutrional requirements among insects are certainly not the same depending on insect classification and actually different from species to species however in general there are major nutritional requirements that must available in an insect artificial diet. The nutrional requirements of insects and substances that commonly available in an artificial diet composition for insect are discussed in this article review.